PENGARUH PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM HAY BARBERSHOP PEKANBARU TERHADAP KEPUTUSAN PEMBELIAN JASA - Wiliam Suryo Lakosono; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Promotional activities to date are still very necessary in influencing a person's attitude in introducing a product or service, especially the use of media in the promotional means. In this case, the most accessed promotional media is Instagram. Instagram itself is a social media that has a great opportunity for business activities because it makes it easier for business people to market their products through sharing photos or videos, to be directly accessible to consumers, as done by Hay Barbershop in promoting its services. The purpose of this study was to see if promotion through Instagram social media had a significant effect on purchasing decisions at Hay Barbershop. Thisresearchusesquantitativeresearchwithexplanatorymethods.Thesamplesinthisstudyw erecustomersofHayBarbershopPekanbaruwithpurposivesamplingtechnique,withatotalsample of100samplescalculatedusingtheslovinformula.Thet-testandcoefficientofdetermination were usedasdataanalysistechniquesinthisstudy. The findings revealed that social media promotion (X) had a positive and significant impact on purchasing decisions (Y). This is demonstrated by tcount> ttable (13.038 > 1.984), the significance is less than 0.05 (0.000 0.05), and the coefficient of determination is positive at 0.634. The hypothesis "Promotion via Instagram social media has a significant effect on purchasing decisions at Hay Barbershop" is then proven. The magnitude of the influence of promotion via Instagram social media on purchasing decisions is 63.4 percent, with the remaining 36.6 percent influenced by other factors not included in the study. Keywords: Promotion, Instagram, Purhcase Decisionza